LINGUOPRAGMATIC CHARACTERISTICS OF ONOMATOPOEIC UNITS IN ENGLISH AND UZBEK LANGUAGES - Nosirova Naima Abduraxmonovna (TADQIQOTLAR, 2025)
Abstract This article provides a comparative analysis of the linguopragmatic properties of onomatopoeia in English and Uzbek. The study examines the phonetic, morphological, and semantic aspects of imitative words in the two languages, as well as their use in sociocultural contexts. The results of the study, conducted using corpus linguistics and sociolinguistic methods, showed that onomatopoeia in English are more common in short and isolated forms ("pop", "bang"), while those in Uzbek are more common in repetitive and rhythmic forms ("gʻir-gʻir", "shov-shov"). In addition, it was found that onomatopoeia in English is used mainly in the media and advertising, and in Uzbek in folklore and everyday speech. The results of the study are of practical importance in improving language teaching methods, translation theory, and intercultural communication. The article analyzes the role of onomatopoeia in language culture and the mechanisms for expressing national worldviews through them. It is recommended to conduct research in this area from the perspective of cognitive linguistics in the future.